The fall - Nix, Garth (New York : Lucas Books/Scholastic Inc., 2000)
Tal has led a sheltered life in a mysterious castle of seven towers, but all that changes when danger strikes.
9-12.
5.
Accelerated Reader AR
Reading Counts RC
Keywords: Responsibility in adolescence -- Juvenile fiction; Theft -- Juvenile fiction; Castles -- Fiction; Good and evil -- Fiction; Fantasy; Fantasy fiction; Fantasy fiction; Fiction; Juvenile works; Children's stories, Australian; Adventure stories, Australian; Children's stories, Australian; Fantasy fiction, Australian; Children's stories